Analisis Pengaruh Model Aisas Terhadap Keputusan Pembelian Generasi Z Pada E-Commerce Shopee di Kota Bandung - Pribadi, Michael Agusto Lemuel; Sirait, Tongam (Green Publisher Indonesia, 2025)
This study examines the impact of the AISAS model (Attention, Interest, Search, Action, Share) on Generation Z's purchase decisions on the Shopee e-commerce platform in Bandung. Using a quantitative approach with a descriptive research design, the research analyzes the behavior of Generation Z consumers, who are digital natives, in making online purchases. The findings indicate that the Action variable has the most significant influence on purchase decisions, followed by Interest and Attention, while Share has a secondary role in reinforcing the purchase decision. The study demonstrates that the AISAS model is effective in explaining Generation Z's online shopping behavior, with significant contributions from user-friendly transactions, promotions, and social media interaction. The research emphasizes the importance of integrating digital marketing strategies with user experiences to attract and retain Generation Z consumers.